Penerapan Terapi Inhalasi Nebulizer pada Pasein dengan Bersihan Jalan Napas Tidak Efektif Akibat Community-Acquired Pneumonia - Asti Permata Yunisa Wabang; Yoany Maria Vianney Bita Aty; Gadur Blasius; Florentianus Tat (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Community acquired Pneumonia is a type of Pneumonia that is acquired in the community. The incidence of Pneumonia in Indonesia in 2013 ranged from 23%-27% and mortality was 1.19%. From 2015-2018 confirmed cases of Pneumonia in children under 5 years were recorded at 505,331 patients with 425 patients dying. The prevalence of Pneumonia in Bali Province in 2018 there were 20,560 cases found based on a history of diagnosis by health workers and / or symptoms that had been felt by respondents / patients. Analyze the effect of the application of Nebulizer inhalation therapy in patients with ineffective airway clearance problems due to Community acquired Pneumonia (CAP). Using case study design with the implementation of nursing care from assessment, diagnosis, intervention, implementation, and evaluation. This study was conducted at RSUP Prof. Dr. I.G.N.G NGOERAH, Denpasar Bali, in July 2023. The results of the analysis showed changes in the patient's respiratory status after administration of Nebulizer inhalation therapy.  The result is clear white mucus discharge and not viscous; respiratory rate decreased, ronchi sounds decreased, and SPO2 status: 98%, patients appeared calmer. Nebulizer inhalation therapy is effective in overcoming airway clearance problems is not effective in Pneumonia patients, especially CAP.